The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s13018-020-02019-4
|View full text |Cite
|
Sign up to set email alerts
|

Distally based peroneal artery perforator-plus fasciocutaneous flap in the reconstruction of soft tissue defects over the distal forefoot: a retrospectively analyzed clinical trial

Abstract: Background Distally based peroneal artery perforator-plus fasciocutaneous (DPAPF) flaps are widely used for reconstructing soft-tissue defects of the lower extremity. However, reports on the reconstruction of the defects over the distal forefoot using the DPAPF flaps are scarce. Herein, we describe our experience on the reconstruction of these defects using DPAPF flaps in a considerable sample size. Methods Between February 2005 and August 2019, a total of 56 DPAPF flaps in 56 patients were used to reconstru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Through a large sample study, Peng et al found that the peroneal artery perforator‐plus fasciocutaneous flap can also effectively repair soft tissue defects in the distal foot. 21 During the average follow‐up of 17.2 months, they found almost no obvious complications, which also provides a new idea for the repair of soft tissue defects in the distal foot. During our procedure, the average time from lift‐up to grafting to the donor site of the big toe was about 45 min, which highlights the convenience and speed of the SCIP flap.…”
Section: Discussionmentioning
confidence: 87%
“…Through a large sample study, Peng et al found that the peroneal artery perforator‐plus fasciocutaneous flap can also effectively repair soft tissue defects in the distal foot. 21 During the average follow‐up of 17.2 months, they found almost no obvious complications, which also provides a new idea for the repair of soft tissue defects in the distal foot. During our procedure, the average time from lift‐up to grafting to the donor site of the big toe was about 45 min, which highlights the convenience and speed of the SCIP flap.…”
Section: Discussionmentioning
confidence: 87%
“…The proximal edge of the flap should not extend beyond the popliteal fossa, and the lateral edges should not extend beyond the lateral midlines in paediatric patients. The DBSF flaps were harvested with the anterograde-retrograde method, which has been described in detail [ 37 , 38 ]. The lesser saphenous vein and the sural nerve must be included as an axis line.…”
Section: Methodsmentioning
confidence: 99%